Promoting Democratization and Good Governance: Rifka Annisa Women Crisis Centre Yogyakarta - FADLURRAHMAN, LALU (Universitas Muhammadiyah Yogyakarta, 2012)
Since the reformation era in 1998, the number of Non-Governmental Organizations in Indonesia is exploding and their impact on Governance growing. Decentralization Policy has supported this trend with its goal to enhance development in the regions, requiring more active involvement of the people in formulating their interests. Organizations can play an important role in the regions as a bridge between the people and the government. In order to strengthen that role, Non-Governmental Organizations must have a solid organisational fundament and political strategies to get actively involved in the policy making process. An additional stronger legal fundament for such an active role could force the government agencies to include NGOs in the part a policy process. This paper deliversa case study on the actual performance of a local Non-Governmental Organization in the field of Gender Politics and Good Governance. Organisational set up and results of attempts to play an active role in articulating the interests of people it represents are reviewed and lead to suggestions for improvement of performance, that can work as guideline for other NGOs in Indonesia who want to contribute to local Governance.Keywords: Civil Society, Good Governance, NGOs, Rifka Annisa Women Crisis Centre